1991
DOI: 10.1093/ejo/13.4.329
|View full text |Cite
|
Sign up to set email alerts
|

An extra X chromosome effect on craniofacial morphogenesis in men

Abstract: A comparative study of the craniofacial complex in men with an extra X chromosome, and normal male and female individuals was carried out using cephalometric radiography. The anterior cranial base, anterior and posterior facial height, maxillary base and ascending ramus were found to be significantly decreased in men with Klinefelter syndrome when compared to the male control group. Significant differences in the lengths of mandibular base and posterior cranial base were not found. When compared to the female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies of 47,XXY males, or males with an extra X chromosome, indicate that their craniofacial linear growth was somewhat reduced relative to that of normal males, but was still greater than in females (Babić et al, 1991;Brown et al, 1993) and they also showed increased height (Varrela, 1984). By contrast, the extra Y chromosome in 47,XYY males defi nitely increases craniofacial growth (Grön et al, 1997) and their height is also remarkably increased relative to normal males or 47,XXY males (Varrela and Alvesalo, 1985).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies of 47,XXY males, or males with an extra X chromosome, indicate that their craniofacial linear growth was somewhat reduced relative to that of normal males, but was still greater than in females (Babić et al, 1991;Brown et al, 1993) and they also showed increased height (Varrela, 1984). By contrast, the extra Y chromosome in 47,XYY males defi nitely increases craniofacial growth (Grön et al, 1997) and their height is also remarkably increased relative to normal males or 47,XXY males (Varrela and Alvesalo, 1985).…”
Section: Discussionmentioning
confidence: 94%
“…These genes are isolated in various parts of the X chromosome (Ogata and Matsuo, 1993). Babić et al (1991), in their study of the effect of an extra X chromosome on craniofacial morphology in men with Klinefelter syndrome or 47,XXY males, hypothesized that their craniofacial dimensions were probably associated with a reduced expression of the genes on the long arm of the Y chromosome, due to the presence of the double dose of the X chromosome genes.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between the number of X chromosomes and craniofacial morphology has been demonstrated in studies of males with Klinefelter syndrome (47XXY karyotype) and women with Turner syndrome (45X). These investigations show that loss or addition of an X chromosome produces opposite effects on cranial base angulation and thereby on facial prognathism (Gorlin et al, 1965;Jensen, 1974;Ingerslev and Kreiborg, 1978;Babic et al, 1991Babic et al, , 1993Brown et al, 1993) The present investigation gives a detailed description of craniofacial variables in prepu-Age (years) bertal girls with various karyotypes of Turner syndrome in order to gain further insight into the relationship between X-chromosome aberration and craniofacial morphology.…”
Section: Introductionmentioning
confidence: 79%
“…Early studies focused on craniofacial features of KS adults, describing a prominent facial profile particularly noticeable in the mandible (Brown et al, ) and noting a decreased anterior and posterior facial height (Babić et al, ), a smaller calvarium, and larger gonial angle (Ingerslev and Krieborg, ). An increase in mandibular and maxillary prognathism (protrusion of the jaw) has also been observed, which the authors attributed to a smaller cranial base angle (Ingerslev and Krieborg 1978).…”
Section: Musculoskeletal Morphologymentioning
confidence: 99%